Methylation of the FKBP5 gene in association with FKBP5 genotypes, childhood maltreatment and depression - Klinger-König, Johanna; Hertel, Johannes; Van der Auwera, Sandra; Frenzel, Stefan; Pfeiffer, Liliane; Waldenberger, Melanie; Golchert, Janine; Teumer, Alexander; Nauck, Matthias; Homuth, Georg; Völzke, Henry; Grabe, Hans J (Neuropsychopharmacology (New York, N.Y.), 2019)
DNA methylation of the FKBP5 gene is assumed to alter FKBP5 expression and hence the synthesis of the FK506 binding protein 51, a central element of a genomic negative feedback loop for glucocorticoid receptor signaling. The present study aimed to replicate and extend previously reported influences of FKBP5 genotypes, childhood maltreatment and depression on methylation levels of five CpG sites in intron 7 of the FKBP5 gene in a large population-based sample. Besides the single nucleotide polymorphism (SNP) rs1360780, associations of the FKBP5 methylation with 22 other, unlinked FKBP5 SNPs as well as associations between FKBP5 methylation levels and transcription levels were investigated. Using whole-blood methylation of 3965 subjects of the Study of Health in Pomerania (SHIP) reduced methylation levels in TT allele carriers of rs1360780 (OR = 0.975, p = .005) and currently depressed subjects (OR = 0.995, p = 0.005) were found. Further, an impact of two yet undescribed SNPs (rs6910300, rs7771727) on methylation levels was observed. However, main and interactive effects for childhood maltreatment and lifetime major depressive disorder observed in previous studies could not be replicated. Finally, FKBP5 methylation levels were not related to FKBP5 transcription levels in whole blood. Thus, the present study verified the associations of FKBP5 genotypes and state depression on the FKBP5 methylation levels of five CpG sites in intron 7. However, FKBP5 methylation of these five CpG sites could not be validated as a valuable clinical biomarker for biological long-term effects of childhood maltreatment or lifetime depression.